2013
DOI: 10.3892/ol.2013.1178
|View full text |Cite
|
Sign up to set email alerts
|

Nail alterations as a surrogate marker for the efficacy of low-dose metronomic chemotherapy

Abstract: Docetaxel is a well-known causative agent of nail alterations. The aim of this study was to reveal the impact of nail alterations associated with low-dose metronomic (LDM) docetaxel chemotherapy on the survival of non-small cell lung cancer (NSCLC) patients. Clinical information, survival data and nail alterations in patients treated with LDM docetaxel chemotherapy (docetaxel 15 mg/m2 per week) were retrospectively reviewed. Forty-nine patients were included in this study. Various nail alterations were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…This suggests that changes in TOF are solely caused by structural transformations in the composition of the fingernail rooting from the fingernail bed. It was observed that the weekly dosed patients, as opposed to the biweekly dosed patients, had more cases of onycholysis and discoloration, as well as larger scaling values for numbness which correlates with the results performed by Kibata et al …”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This suggests that changes in TOF are solely caused by structural transformations in the composition of the fingernail rooting from the fingernail bed. It was observed that the weekly dosed patients, as opposed to the biweekly dosed patients, had more cases of onycholysis and discoloration, as well as larger scaling values for numbness which correlates with the results performed by Kibata et al …”
Section: Discussionsupporting
confidence: 80%
“…[4][5][6] Kibata et al demonstrated that the incidence and severity of fingernail changes were related to the number of docetaxel chemotherapy administrations. 7 Highfrequency ultrasound has been reported to be an effective tool for quantitative evaluation of fingernail condition and microstructure. [8][9][10][11][12] The aim of the present study was to examine whether chemotherapeutic treatment progression can be correlated quantitatively with the alterations in fingernail ultrasonic properties, by measuring the changes in the time-of-flight (TOF) parameter during the course of chemotherapy regimens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation